2020
DOI: 10.1101/2020.06.17.156307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for distinct inflammasome complex assembly by human NLRP1 and CARD8

Abstract: Nod-like receptor (NLR) proteins activate pyroptotic cell death and IL-1 driven inflammation by assembling and activating the inflammasome complex. Closely related NLR proteins, NLRP1 and CARD8 undergo unique auto-proteolysis-dependent activation and are implicated in auto-inflammatory diseases; however, the molecular mechanisms of activation are not understood. Here we report the structural basis of how the activating domains (FIIND UPA -CARD) of NLRP1 and CARD8 self-oligomerize to trigger the assembly of dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…In contrast to free UPA 28,29 , the FIIND was monomeric in solution (Extended Data Fig. 8g), which suggests that the ZU5 domain inhibits UPA dimerization or oligomerization.…”
Section: Inhibition Of Upa-card Oligomerization By Zu5mentioning
confidence: 99%
“…In contrast to free UPA 28,29 , the FIIND was monomeric in solution (Extended Data Fig. 8g), which suggests that the ZU5 domain inhibits UPA dimerization or oligomerization.…”
Section: Inhibition Of Upa-card Oligomerization By Zu5mentioning
confidence: 99%
“…Despite maintaining FIIND autoprocessing, interface III mutations completely abolished inflammasome activity, even in the presence of the activating ligand VbP (Figure 3D). We reasoned that the observed UPA-UPA interface might be preserved on the inflammasome filament, as the UPA itself promotes CARD oligomerization and inflammasome activity (Hollingsworth et al, 2020a; Qin et al, 2020). Additionally, NLRP1 interface III mutations abolished inflammasome signaling in cells (Hollingsworth et al, 2020b) and disrupted filament formation in vitro (Huang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that our studies suggest that CARD8 and NLRP1 may have also both evolved to sense a single endogenous danger signal triggered by DPP8/9 inhibition. Another important difference between CARD8 and NLRP1 is the structure of assembled inflammasome: while CARD8 can only directly recruit caspase-1 and activate rapid pyroptosis without causing cytokine maturation, NLRP1 recruits caspase-1 via ASC to elicit an inflammatory signaling cascade with cytokine secretion and pyroptotic cell death (Ball et al, 2020; Hollingsworth et al, 2020a; Qin et al, 2020). In this context, it is possible that NLRP1 activation is more pro-inflammatory, as exemplified by the association of NLRP1 hyperactivation with a series of severe skin pro-inflammatory diseases (Grandemange et al, 2017; Jin et al, 2007; Levandowski et al, 2013; Zhong et al, 2016; Zhong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that the same UPA-UPA interaction surface as observed in the 2:1 NLRP1-DPP9 complex is utilized in the higher order UPA-CARD filament. Indeed, negative staining EM showed that the wild-type UPA-CARD of hNLRP1 formed filamentous structures 25,26 (Fig. 5b), but not the UPA-UPA interface mutants, UPA-CARD P1278E and UPA-CARD L1281E (Fig.…”
Section: Structural Basis For Zu5-mediated Inhibition Of Upa-card Olimentioning
confidence: 98%